2011
DOI: 10.1055/s-0031-1290100
|View full text |Cite
|
Sign up to set email alerts
|

Indium(III) Chloride Catalyzed Convergent, Regioselective Synthesis of Annulated Quinoline and Pyridine Derivatives

Abstract: A direct convergent two-component regioselective synthesis of annulated pyridine motif from 1-aminopenta-1,4-diene fragment and aromatic aldehyde by indium(III) chloride catalyzed reaction has been developed through a concerted pathway. A series of potentially bioactive pyranoquinoline, phenanthroline, and pyridopyrimidine derivatives has been synthesized in high yields by this protocol.The pyridine and quinoline derivatives play a central role as versatile building blocks of many natural products. 1 Many meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In 2012, Majumdar et al, reported the synthesis of pyrido [3,2- f ]coumarins 168a – f by the Indium (III) chloride-catalyzed reaction of 5-allyl-6-aminocoumarin ( 167 ) with benzaldehydes 51 [ 123 ]. In the proposed mechanism, the imine A formed from 167 and 51a in the presence of InCl 3 at first, followed by an 1,5-H shift to the intermediate B .…”
Section: Synthetic Strategies For the Preparation Of Fused Pyridocoum...mentioning
confidence: 99%
“…In 2012, Majumdar et al, reported the synthesis of pyrido [3,2- f ]coumarins 168a – f by the Indium (III) chloride-catalyzed reaction of 5-allyl-6-aminocoumarin ( 167 ) with benzaldehydes 51 [ 123 ]. In the proposed mechanism, the imine A formed from 167 and 51a in the presence of InCl 3 at first, followed by an 1,5-H shift to the intermediate B .…”
Section: Synthetic Strategies For the Preparation Of Fused Pyridocoum...mentioning
confidence: 99%